2008
DOI: 10.1105/tpc.107.057851
|View full text |Cite
|
Sign up to set email alerts
|

Sphingolipid Long-Chain Base Hydroxylation Is Important for Growth and Regulation of Sphingolipid Content and Composition inArabidopsis 

Abstract: Sphingolipids are structural components of endomembranes and function through their metabolites as bioactive regulators of cellular processes such as programmed cell death. A characteristic feature of plant sphingolipids is their high content of trihydroxy long-chain bases (LCBs) that are produced by the LCB C-4 hydroxylase. To determine the functional significance of trihydroxy LCBs in plants, T-DNA double mutants and RNA interference suppression lines were generated for the two Arabidopsis thaliana LCB C-4 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
196
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(203 citation statements)
references
References 49 publications
7
196
0
Order By: Relevance
“…Such data are starting to emerge regarding the role of phytosphingosine (Coursol et al, 2005;Shi et al, 2007;Chen et al, 2008) and also D8-unsaturated LCBs (Ryan et al, 2007). The significance of sphingolipids and their phosphorylated metabolites is still an evolving story in many eukaryotic systems, and it is hoped that studies such as this can contribute to the development of more precise models for their form and function in different organisms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such data are starting to emerge regarding the role of phytosphingosine (Coursol et al, 2005;Shi et al, 2007;Chen et al, 2008) and also D8-unsaturated LCBs (Ryan et al, 2007). The significance of sphingolipids and their phosphorylated metabolites is still an evolving story in many eukaryotic systems, and it is hoped that studies such as this can contribute to the development of more precise models for their form and function in different organisms.…”
Section: Resultsmentioning
confidence: 99%
“…In that respect, it is interesting that Coursol et al (2005) reported a different LCB-1-P, phytosphingosine-1-P (t18:0-1-P), as being involved in Arabidopsis guard cell closure. Very recently, Chen et al (2008) demonstrated a crucial role for these C4-hydroxylated LCBs in Arabidopsis growth and development.…”
Section: Phenotypic Characterization Of Arabidopsis Insertion Mutantsmentioning
confidence: 99%
“…Sphingolipids are essential regulators not only of cell death, but also of development in both animal and plant cells (Teufel et al 2009;Chen et al 2008). This notion is supported by the various developmental defects in mutants with compromised very long-chain fatty acids that are components of sphingolipids and in mutants with impaired hydroxylation of long-chain bases (Bach et al 2008;Zheng et al 2005;Chen et al 2008). It could be that all mutants, being in loh2 background that lacks certain complex sphingolipids, are unable to proceed into mature plants when AAL toxin is present.…”
Section: Resultsmentioning
confidence: 99%
“…In the plenary talk of this session (E. Cahoon, O44), it was reported that complete elimination of sphingolipid synthesis results in loss of Golgi bodies and aberrant ER morphology in pollen, leading to male gametophytic lethality [26]. In addition, complete or partial reductions in sphingolipid long-chain base (LCB) C-4 hydroxylation in Arabidopsis were shown to result in increases in total sphingolipid content due to the accumulation of sphingolipids with C16 species (E. Cahoon, O44) [27]. This structural modification was also shown to be important for growth of Arabidopsis (E. Cahoon, O44) and reproductive potential of rice (T. Imamura, P100) [28].…”
Section: Sphingolipids Sterols Isoprenoidsmentioning
confidence: 99%